Agricultural and urban land use intensifies riverine GHG emissions across continents - Diego Panique-Casso; Samuel Bodé; Matti Barthel; Seid Tiku Mereta; Thu Huong Thi Hoang; Ruben Jerves-Cobo; Pascal Boeckx; Johan Six; Peter Goethals; Long Ho (Water Research, 2026)

Limited human mobility during the Neolithic period in the Meuse and Mons basin in Belgium: multi-element isotopic analysis - IJk van Hattum; Marta Costas-Rodríguez; Kasper Hobin; Prudence Robert; Frank Vanhaecke; Elliot Van Maldegem; Hélène Collet; Pierre Cattelain; Michel Toussaint; Hans Vandendriessche; Samuel Bodé; Pascal Boeckx; et al. (Archaeological and Anthropological Sciences, 2026)
While the introduction of the Neolithic way of life in central Belgium around 5300 BCE is well-documented, the provenance and mobility patterns of Middle to Final Neolithic groups in southern Belgium (Wallonia) remain unclear. This work presents the first multi-element isotopic (strontium, 87 Sr/ 86 Sr; oxygen, δ 18 O; carbon, δ 13 C) data from prehistoric human dental enamel from the region. The study includes a total of 29 individuals, coming from karstic caves in the Meuse basin, the mining complex of Spiennes, and the megalithic tomb of Wéris II. The study also explores the variability of bioavailable strontium ratios in the geologically heterogeneous Meuse basin using modern plants. The analysis of multi-element isotopic data reveals high δ 18 O values and diverse 87 Sr/ 86 Sr ratios. The findings suggest that these individuals likely originated from or spent their childhood in present-day Belgium. Furthermore, the study highlights limited mobility during the Final Neolithic period, characterized by a combination of local residency and potential short-distance mobility or post-mortem movements. Overall, this study provides the first δ 18 O values from ancient human remains in the region and reshapes our understanding of human mobility during the Neolithic in present-day Belgium.

Unveiling the important roles of sludge worms (Tubifex tubifex) in wetland carbon and nitrogen cycling: Implications for greenhouse gas emissions in a warming climate - Long Ho; Kim Pham; Andries Debognies; Samuel Bodé; Pieter Vermeir; Pascal Boeckx; Jo De Vrieze; Peter Goethals (Water Research, 2026)

Canopy Microclimate and Leaf Traits Shape Interspecies Variation in Photosynthetic Temperature Responses of Evergreen Tropical Trees in the Congo Basin - Thomas Sibret; Félicien Meunier; Kristine Y. Crous; Sarah Lamotte; Marc Peaucelle; Louise Terryn; Pieter De Frenne; Ivan Janssens; Bernard Bonyoma; Hans Verbeeck; Marijn Bauters; Pascal Boeckx (Global Change Biology, 2026)
Tropical forests contribute disproportionately to global carbon cycling, yet their resilience under climate warming remains uncertain, partly due to limited understanding of leaf‐level temperature responses of photosynthesis. In particular, the role of fine‐scale canopy microclimate in shaping photosynthetic temperature responses in tropical trees has been overlooked. We quantified vertical microclimate variation and measured leaf‐level photosynthetic temperature responses in 13 coexisting evergreen tree species spanning the full canopy profile in a lowland Congo Basin forest. Leaf gas exchange measurements were integrated with structural leaf traits and high‐resolution microclimate profiles to assess how temperature conditions and ecological strategies shape photosynthetic responses. Photosynthetic traits, including the light‐saturated photosynthetic rate at the temperature optimum and stomatal conductance at the temperature optimum, increased with canopy height, with pioneer species showing steeper increases than non‐pioneers. The temperature optimum of photosynthesis ( T opt ) was positively related to both mean and maximum leaf temperature ( T leaf ), driven mainly by interspecific differences rather than intraspecific plasticity. This suggests that T opt reflects species‐level adaptation to the temperature conditions of their canopy niche rather than leaf‐level adjustment to local microclimate. Stomatal conductance influenced T leaf via transpiration and thereby contributed to shaping T opt . Leaves experiencing larger temperature fluctuations showed reduced sensitivity, reflected in a broader photosynthetic temperature‐response width ( Ω ). Ω was also positively associated with structural traits such as leaf mass per area and leaf dry matter content, both within and among species, indicating that greater structural investment helps sustain higher photosynthetic rates across wider temperature ranges and enhances tolerance to temperature variability. By linking canopy microclimate, physiological traits, and structural characteristics, our findings demonstrate how vertical microclimatic gradients and functional diversity jointly determine photosynthetic temperature responses in tropical forest trees. Incorporating leaf‐level temperature regimes, stomatal regulation, and trait variation into vegetation models could improve predictions of tropical forest carbon dynamics under climate change.

Bridging the gap in riverine greenhouse gas research: From monitoring methods to mechanistic understanding - Long Ho; Matti Barthel; Samuel Bodé; Diego Panique-Casso; Johan Six; Pascal Boeckx; Peter Goethals (Journal of Environmental Management, 2026)

Congo Basin Carbon Cycle Responses to Global Change - Sarah Worden; Rong Fu; A. Anthony Bloom; Marijn Bauters; Hans Verbeeck; Temilola Fatoyinbo; Wannes Hubau; Lydie‐Stella Koutika; Steve Kwatcho Kengdo; Sybryn L. Maes; Vincent Medjibe; Nicholas J. Russo; et al. (Global Change Biology, 2026)
The Congo Basin and its contiguous forests harbor globally significant carbon stocks, estimated at 65 gigatons of C (GtC) above and belowground. Despite rising temperatures and intensifying droughts, they have remained a carbon sink, albeit weak: 0.26–0.50 GtC yr. −1 carbon uptake since 1980. However, these forests' carbon stocks and fluxes, including gross primary productivity, respiration, net primary productivity, and riverine carbon transport, remain poorly quantified. This limits understanding of the region's role in the global carbon cycle, its vulnerability to environmental change, and its potential as a long‐term carbon sink. We review and quantify Congo Basin and contiguous forest carbon stocks and fluxes and synthesize the current knowledge on how key global change drivers shape the region's carbon cycle. We find limited responses to long‐term precipitation variability, but declining stocks and fluxes in response to long‐term and increasing temperature and drought frequency. Land cover and land use changes, largely driven by small‐scale agriculture, logging, and agro‐industrial expansion, reduce carbon stocks, ecosystem structure and functioning, and animal‐mediated ecosystem services. In contrast, large‐scale savanna biomass burning delivers phosphorus and nitrogen to Congo Basin forests via cross‐equatorial winds, providing additional nutrients and supporting carbon sequestration. In situ studies suggest that CO 2 fertilization has increased intrinsic water‐use efficiency, although its effects may be modulated by climate change, and its impacts on biomass accumulation remain uncertain. Legacy effects from historical land use and climate change likely shaped present‐day vegetation structure, yet their relative influence is unclear. High‐resolution carbon monitoring, improved remote sensing, and strengthened in situ measurement networks are needed to quantify the impacts of these key drivers and their interactions on the Central African carbon cycle. This is needed to inform conservation strategies and advance understanding of the region's future as a carbon sink under global change pressures.

Dual use of isotopic and environmental proxy approaches to trace nitrate sources and biogeochemical pathways in an agro-industrially influenced river basin - Ioannis Matiatos; Elias Dimitriou; Anastasios Papadopoulos; Konstantinos Lazogiannis; Nikolaos Th. Skoulikidis; Ioannis Karaouzas; Leonidas Vardakas; Sergios Lagogiannis; Ioanna Zotou; Vasiliki Paraskevopoulou; Pascal Boeckx (Science of The Total Environment, 2025)

Interplay between temperature and redox conditions regulates wetland biogeochemistry and greenhouse gas emissions - Long Ho; Kim Pham; Andries Debognies; Samuel Bodé; Pieter Vermeir; Pascal Boeckx; Jo De Vrieze; Peter Goethals (Science of The Total Environment, 2025)

The prospects of replacing the sensory coffee quality assessment methods with objective, instrument-based approaches: A review - Markos Makiso Urugo; Mohammed Worku; Tessema Astatkie; Pascal Boeckx; Yetenayet B. Tola; Paulos Getachew (Trends in Food Science & Technology, 2025)

Chemical and microbiological analysis of urban and associated natural water systems of inhabited volcanic islands of the Galapagos (Ecuador) - Lenin Riascos-Flores; Long Ho; Wout Van Echelpoel; Marie Anne Eurie Forio; Stijn Bruneel; Niels De Troyer; Nancy de Saeyer; Rafael Bermudez; Wim Vanden Berghe; Luis Dominguez-Granda; Pascal Boeckx; Christine Van der heyden; et al. (Water Research, 2025)

Gross soil phosphorus fluxes remain constant along forest recovery trajectories in Central Africa - Viktor Van de Velde; Lucia Fuchslueger; Judith Prommer; Jonathan Bachiseze Magala; Joseph Lokana Mande; Sebastian Doetterl; Isaac Ahanamungu Makelele; Wolfgang Wanek; Samuel Bodé; Andreas Richter; Marijn Bauters; Pascal Boeckx (Soil Biology and Biochemistry, 2025)

Controls on the geochemical composition of surface water in Alfeios River basin in the transition era of lignite mine closure at Megalopolis, Greece - Christos Drougas; Efstratios Kelepertzis; Zacharenia Kypritidou; Evangelia Sigala; Ioannis Matiatos; Elissavet Dotsika; Eleni Vasileiou; Georgios Louloudis; Eleni Mertiri; Pascal Boeckx; Evangelos Oikonomopoulos; Christos Roumpos (Science of The Total Environment, 2025)

Weeding force saving to improve profitability of cassava-legumes cropping systems in eastern Democratic Republic of the Congo - Audry Muke; Leon Nabahungu; Kokou Kinché; Bernard Vanlauwe; Pascal Boeckx (Crop Protection, 2025)

Tracing the trail of eroded fertile soils during a high intensity rainfall event: A fingerprinting study in war-torn tropical mountains - Ivan Lizaga; Montfort Bagalwa; Borja Latorre; Kristof Van Oost; Ana Navas; William Blake; Pascal Boeckx (Journal of Environmental Management, 2025)

Control of landscape position on organic matter decomposition via soil moisture during a wet summer - Astrid Françoys; Haichao Li; Orly Mendoza; Kevin Dewitte; Samuel Bodé; Pascal Boeckx; Wim Cornelis; Stefaan De Neve; Steven Sleutel (Soil and Tillage Research, 2024)

Nitrogen fertilizer classification using multivariate fingerprinting with stable isotopes - Pieterjan De Bauw; Samuel Bodé; Maaike Perneel; Dominique Billard; Pascal Boeckx (Nutrient Cycling in Agroecosystems, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Unravelling CH4 and N2O dynamics in tidal wetlands using natural abundance isotopes and functional genes - Long Ho; Kim Pham; Matti Barthel; Stephen Harris; Samuel Bodé; Jo De Vrieze; Pieter Vermeir; Johan Six; Pascal Boeckx; Peter Goethals (Soil Biology and Biochemistry, 2024)

Pottery use across the Neolithic transition in northern Belgium: evidence from isotopic, molecular and microscopic analysis - Dimitri Teetaert; Marieke Vannoorenberghe; Thomas Van de Velde; Mathieu Boudin; Samuel Bodé; Lucy Kubiak-Martens; Mathijs Baert; Frederic Lynen; Philippe Crombé; Pascal Boeckx (Archaeological and Anthropological Sciences, 2024)
This study represents the first extensive residue analysis of prehistoric pottery from northern Belgium. It examines pottery use and culinary practices across the Mesolithic-Neolithic transition, from the late 6th to the early 4th millennium cal BC. Residue analyses were performed on more than 200 samples from nine archaeological sites, representing different cultural groups from this transitional phase. This includes the analysis of charred food residues encrusted on the vessel surfaces by elemental analysis-isotope ratio mass spectrometry (EA-IRMS), gas chromatography-mass spectrometry (GC-MS), stereomicroscopic analysis and Scanning Electron Microscopy (SEM), as well as the analysis of absorbed lipids by gas chromatography-combustion-isotope ratio mass spectrometry (GC-C-IRMS). This study provides the first evidence of ruminant dairy fats in Early Neolithic Limburg pottery, supporting the hypothesis that this pottery was produced and used by LBK farmers rather than hunter-gatherer populations. The first indigenous pottery of the Swifterbant culture was frequently used to process freshwater fish (often together with plant foods) and ruminant meat, although several of the studied vessels likely contained mixtures of resources which could also include porcine products. Ruminant dairy is nearly absent from this pottery. Similar results were obtained for pottery of the subsequent Michelsberg culture/Group of Spiere of the late 5th and early 4th millennium cal BC. The limited presence of ruminant dairy fats in this pottery contrasts with the findings for Middle Neolithic pottery from neighbouring regions, providing further evidence for the existence of regional variations in pottery use or culinary practices throughout prehistoric NW Europe. However, our current view of pottery use during the Mesolithic-Neolithic transition in northern Belgium might be biased by the difficulties in distinguishing between wild and domesticated ruminant adipose fats as well as in detecting plant foods through lipid residue analysis.

Environment and microbiome drive different microbial traits and functions in the macroscale soil organic carbon cycle - Daniel Wasner; Joerg Schnecker; Xingguo Han; Yifei Sun; Aline Frossard; Erick Zagal Venegas; Pascal Boeckx; Sebastian Doetterl (Global Change Biology, 2024)
Soil microbial traits and functions play a central role in soil organic carbon (SOC) dynamics. However, at the macroscale (regional to global) it is still unresolved whether (i) specific environmental attributes (e.g., climate, geology, soil types) or (ii) microbial community composition drive key microbial traits and functions directly. To address this knowledge gap, we used 33 grassland topsoils (0–10 cm) from a geoclimatic gradient in Chile. First, we incubated the soils for 1 week in favorable standardized conditions and quantified a wide range of soil microbial traits and functions such as microbial biomass carbon (MBC), enzyme kinetics, microbial respiration, growth rates as well as carbon use efficiency (CUE). Second, we characterized climatic and physicochemical properties as well as bacterial and fungal community composition of the soils. We then applied regression analysis to investigate how strongly the measured microbial traits and functions were linked with the environmental setting versus microbial community composition. We show that environmental attributes (predominantly the amount of soil organic matter) determined patterns of MBC along the gradient, which in turn explained microbial respiration and growth rates. However, respiration and growth normalized for MBC (i.e., specific respiration and growth) were more linked to microbial community composition than environmental attributes. Notably, both specific respiration and growth followed distinct trends and were related to different parts of the microbial community, which in turn resulted in strong effects on microbial CUE. We conclude that even at the macroscale, CUE is the result of physiologically decoupled aspects of microbial metabolism, which in turn is partially determined by microbial community composition. The environmental setting and microbial community composition affect different microbial traits and functions, and therefore both factors need to be considered in the context of macroscale SOC dynamics.

New tree height allometries derived from terrestrial laser scanning reveal substantial discrepancies with forest inventory methods in tropical rainforests - Louise Terryn; Kim Calders; Félicien Meunier; Marijn Bauters; Pascal Boeckx; Benjamin Brede; Andrew Burt; Jerome Chave; Antonio Carlos Lola da Costa; Barbara D'hont; Mathias Disney; Tommaso Jucker; et al. (Global Change Biology, 2024)
Tree allometric models, essential for monitoring and predicting terrestrial carbon stocks, are traditionally built on global databases with forest inventory measurements of stem diameter (D) and tree height (H). However, these databases often combine H measurements obtained through various measurement methods, each with distinct error patterns, affecting the resulting H:D allometries. In recent decades, terrestrial laser scanning (TLS) has emerged as a widely accepted method for accurate, non‐destructive tree structural measurements. This study used TLS data to evaluate the prediction accuracy of forest inventory‐based H:D allometries and to develop more accurate pantropical allometries. We considered 19 tropical rainforest plots across four continents. Eleven plots had forest inventory and RIEGL VZ‐400(i) TLS‐based D and H data, allowing accuracy assessment of local forest inventory‐based H:D allometries. Additionally, TLS‐based data from 1951 trees from all 19 plots were used to create new pantropical H:D allometries for tropical rainforests. Our findings reveal that in most plots, forest inventory‐based H:D allometries underestimated H compared with TLS‐based allometries. For 30‐metre‐tall trees, these underestimations varied from −1.6 m (−5.3%) to −7.5 m (−25.4%). In the Malaysian plot with trees reaching up to 77 m in height, the underestimation was as much as −31.7 m (−41.3%). We propose a TLS‐based pantropical H:D allometry, incorporating maximum climatological water deficit for site effects, with a mean uncertainty of 19.1% and a mean bias of −4.8%. While the mean uncertainty is roughly 2.3% greater than that of the Chave2014 model, this model demonstrates more consistent uncertainties across tree size and delivers less biased estimates of H (with a reduction of 8.23%). In summary, recognizing the errors in H measurements from forest inventory methods is vital, as they can propagate into the allometries they inform. This study underscores the potential of TLS for accurate H and D measurements in tropical rainforests, essential for refining tree allometries.

Regulating greenhouse gas dynamics in tidal wetlands: Impacts of salinity gradients and water pollution - Long Ho; Matti Barthel; Kim Pham; Samuel Bodé; Carl Van Colen; Tom Moens; Johan Six; Pascal Boeckx; Peter Goethals (Journal of Environmental Management, 2024)

Geochemistry and origin of inorganic contaminants in soil, river sediment and surface water in a heavily urbanized river basin - Zacharenia Kypritidou; Efstratios Kelepertzis; Ioannis Kritikos; Emanuela Kapaj; Iro Skoulika; Marios Kostakis; Emmanuel Vassilakis; Sotirios Karavoltsos; Pascal Boeckx; Ioannis Matiatos (Science of The Total Environment, 2024)

Combining isotopic and elemental tracers for enhanced sediment source partitioning in complex catchments - Ivan Lizaga; Borja Latorre; Samuel Bodé; Leticia Gaspar; Pascal Boeckx; Ana Navas (Journal of Hydrology, 2024)

Responses of the soil microbial community structure to multiple interacting global change drivers in temperate forests - Jie Yang; Haben Blondeel; Pascal Boeckx; Kris Verheyen; Pieter De Frenne (Plant and Soil, 2024)

The impact of soil chemistry, moisture and temperature on branched and isoprenoid GDGTs in soils: A study using six globally distributed elevation transects - Cindy De Jonge; Jingjing Guo; Petter Hällberg; Marco Griepentrog; Hamdi Rifai; Andreas Richter; Edson Ramirez; Xinbao Zhang; Rienk H. Smittenberg; Francien Peterse; Pascal Boeckx; Gerd Dercon (Organic Geochemistry, 2024)

Unravelling spatiotemporal N2O dynamics in an urbanized estuary system using natural abundance isotopes - Long Ho; Matti Barthel; Stephen Harris; Kaat Vermeulen; Johan Six; Samuel Bodé; Pascal Boeckx; Peter Goethals (Water Research, 2023)

Stable isotopes reveal organic nitrogen pollution and cycling from point and non-point sources in a heavily cultivated (agricultural) Mediterranean river basin - Ioannis Matiatos; Konstantinos Lazogiannis; Anastasios Papadopoulos; Nikolaos Th. Skoulikidis; Pascal Boeckx; Elias Dimitriou (Science of The Total Environment, 2023)

Drug discovery-based approach identifies new nitrification inhibitors - Fabian Beeckman; Andrzej Drozdzecki; Alexa De Knijf; Mario Corrochano-Monsalve; Samuel Bodé; Pieter Blom; Geert Goeminne; Carmen González-Murua; Sebastian Lücker; Pascal Boeckx; Christian V. Stevens; Dominique Audenaert; et al. (Journal of Environmental Management, 2023)

Impact of salinity gradient, water pollution and land use types on greenhouse gas emissions from an urbanized estuary - Long Ho; Matti Barthel; Diego Panique-Casso; Kaat Vermeulen; Stijn Bruneel; Xingzhen Liu; Samuel Bodé; Johan Six; Pascal Boeckx; Peter Goethals (Environmental Pollution, 2023)

Ground-based climate data show evidence of warming and intensification of the seasonal rainfall cycle during the 1960–2020 period in Yangambi, central Congo Basin - Emmanuel Kasongo Yakusu; Joris Van Acker; Hans Van de Vyver; Nils Bourland; José Mbifo Ndiapo; Théophile Besango Likwela; Michel Lokonda Wa Kipifo; Amand Mbuya Kankolongo; Jan Van den Bulcke; Hans Beeckman; Marijn Bauters; Pascal Boeckx; et al. (Climatic Change, 2023)
Meteorological stations are rare in central Africa, which leads to uncertainty in regional climatic trends. This is particularly problematic for the Congo Basin, where station coverage decreased significantly during the last few decades. Here, we present a digitized dataset of daily temperature and precipitation from the Yangambi biosphere reserve, covering the period 1960–2020 (61 years) and located in the heart of the Congo Basin. Our results confirm a long-term increase in temperature and temperature extremes since the 1960s, with strong upward trends since the early 1990s. Our results also indicate a drying trend for the dry season and intensification of the wet season since the early 2000s. Ongoing warming and increasing precipitation seasonality and intensity already have a significant impact on crop yields in Yangambi. This calls for urgent development of climate-smart and dynamic agriculture and agroforestry systems. We conclude that systematic digitization and climate recording in the Congo Basin will be critical to improve much-needed gridded benchmark datasets of climatic variables.

Global reanalysis products cannot reproduce seasonal and diurnal cycles of tropospheric ozone in the Congo Basin - Inês Vieira; Hans Verbeeck; Félicien Meunier; Marc Peaucelle; Thomas Sibret; Lodewijk Lefevre; Alexander W. Cheesman; Flossie Brown; Stephen Sitch; José Mbifo; Pascal Boeckx; Marijn Bauters (Atmospheric Environment, 2023)

Within and among farm variability of coffee quality of smallholders in southwest Ethiopia - Merkebu Getachew; Pascal Boeckx; Kris Verheyen; Kassaye Tolassa; Ayco J. M. Tack; Kristoffer Hylander; Stijn Luca; Beyene Zewdie; Pieter De Frenne (Agroforestry Systems, 2023)

Effects of shade tree species on soil biogeochemistry and coffee bean quality in plantation coffee - Merkebu Getachew; Kris Verheyen; Kassaye Tolassa; Ayco J.M. Tack; Kristoffer Hylander; Biruk Ayalew; Pascal Boeckx; Dries Landuyt; Pieter De Frenne (Agriculture, Ecosystems & Environment, 2023)

Substantial Organic and Particulate Nitrogen and Phosphorus Export from Geomorphologically Stable African Tropical Forest Landscapes - Simon Baumgartner; Marijn Bauters; Travis W. Drake; Matti Barthel; Serge Alebadwa; Nadine Bahizire; Basile Mujinya Bazirake; Johan Six; Pascal Boeckx; Kristof Van Oost (Ecosystems, 2023)

N2O production by mussels: Quantifying rates and pathways in current and future climate settings - Helena Voet; Karline Soetaert; Tom Moens; Samuel Bodé; Pascal Boeckx; Carl Van Colen; Jan Vanaverbeke (Frontiers in Marine Science, 2023)
Blue mussels ( Mytilus edulis ) are an abundant and economically important species across the North Sea. Partly because of their potent filter feeding and associated shell biofilm, they are able to influence and alter the surrounding marine ecosystem. As a result of proliferating offshore wind farms (OWFs), whose turbine foundations are rapidly colonised by suspension feeding artificial hard substrate communities dominated by M. edulis , as well as planned co-location strategies of these OWFs with mussel mariculture, their numbers will only increase towards the future. On top of these local stressors, global climate change is exerting additional pressure on the marine environment. This study focusses on the link between M. edulis , its microbial shell biofilm and the local nitrogen cycling by quantifying the magnitude and underlying pathways of mussel-associated nitrous oxide (N 2 O) production. A set of closed-core incubations established nitrifier denitrification as the main chemical pathway of M. edulis related N 2 O production, although ammonium, nitrite and nitrate all acted as possible precursors. Additional future-climate experiments revealed that blue mussel’s total N 2 O production, as well as its metabolic activity and the relative contribution of its shell biofilm, were affected by warming (+ 3°C), acidification (- 0.3 pH units), or the combination of both. Because the effects of temperature and acidity were often of an antagonistic nature, the results suggest a relatively small net effect on local N 2 O production in future-climate marine environments. However, N 2 O production rates were several orders of magnitude lower than other measured N species ( NH 4 + , NO 2 − and NO 3 - ), making substantial mussel-associated N 2 production likely. This would greatly affect the local eutrophication levels or even bioavailable nitrogen concentrations.

Assessment of natural and anthropogenic contamination sources in a Mediterranean aquifer by combining hydrochemical and stable isotope techniques - Efstratios Kelepertzis; Ioannis Matiatos; Fotini Botsou; Christina Antonopoulou; Ioannis Lappas; Elissavet Dotsika; Vladislav Chrastný; Pascal Boeckx; Sotirios Karavoltsos; Michael Komárek (Science of The Total Environment, 2023)

Conservative N cycling despite high atmospheric deposition in early successional African tropical lowland forests - Isaac Ahanamungu Makelele; Marijn Bauters; Kris Verheyen; Matti Barthel; Johan Six; Tobias Rütting; Samuel Bodé; Landry Cizungu Ntaboba; Basile Mujinya Bazirake; Faustin Boyemba Bosela; Fabrice Kimbesa; Corneille Ewango; et al. (Plant and Soil, 2022)

Identification of sources and transformations of nitrate in Cr(VI)-impacted alluvial aquifers by a hydrogeochemical and δ15N-NO3− and δ18O-NO3 – isotopes approach - Konstantina Pyrgaki; Efstratios Kelepertzis; Ariadne Argyraki; Pascal Boeckx; Fotini Botsou; Emmanuel Dassenakis (Environmental Science and Pollution Research, 2022)

Patterns of free amino acids in tundra soils reflect mycorrhizal type, shrubification, and warming - Louise C. Andresen; Samuel Bodé; Robert G. Björk; Anders Michelsen; Rien Aerts; Pascal Boeckx; J. Hans C. Cornelissen; Kari Klanderud; Richard S. P. van Logtestijn; Tobias Rütting (Mycorrhiza, 2022)
The soil nitrogen (N) cycle in cold terrestrial ecosystems is slow and organically bound N is an important source of N for plants in these ecosystems. Many plant species can take up free amino acids from these infertile soils, either directly or indirectly via their mycorrhizal fungi. We hypothesized that plant community changes and local plant community differences will alter the soil free amino acid pool and composition; and that long-term warming could enhance this effect. To test this, we studied the composition of extractable free amino acids at five separate heath, meadow, and bog locations in subarctic and alpine Scandinavia, with long-term (13 to 24 years) warming manipulations. The plant communities all included a mixture of ecto-, ericoid-, and arbuscular mycorrhizal plant species. Vegetation dominated by grasses and forbs with arbuscular and non-mycorrhizal associations showed highest soil free amino acid content, distinguishing them from the sites dominated by shrubs with ecto- and ericoid-mycorrhizal associations. Warming increased shrub and decreased moss cover at two sites, and by using redundancy analysis, we found that altered soil free amino acid composition was related to this plant cover change. From this, we conclude that the mycorrhizal type is important in controlling soil N cycling and that expansion of shrubs with ectomycorrhiza (and to some extent ericoid mycorrhiza) can help retain N within the ecosystems by tightening the N cycle.

Predicting Soil Organic Carbon Mineralization Rates Using δ13C, Assessed by Near-Infrared Spectroscopy, in Depth Profiles Under Permanent Grassland Along a Latitudinal Transect in Chile - Hidalgo Marcela; María de los Ángeles Sepulveda; Cristina Muñoz; Manuel Casanova; Daniel Wasner; Samuel Bodé; Sebastian Doetterl; Pascal Boeckx; Erick Zagal (Journal of Soil Science and Plant Nutrition, 2022)

Greenhouse gas dynamics in an urbanized river system: influence of water quality and land use - Long Ho; Ruben Jerves-Cobo; Matti Barthel; Johan Six; Samuel Bode; Pascal Boeckx; Peter Goethals (Environmental Science and Pollution Research, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Spatial variability of iron, zinc and selenium content in faba bean (Vicia faba L.) seeds from central and southwestern highlands of Ethiopia - Frehiwot Sileshi; Amsalu Nebiyu; Maarten Van Geel; Samuel Vanden Abeele; Gijs Du Laing; Pascal Boeckx (Plant and Soil, 2022)

Observing the water handling in humans to resolve the role of the interstitium: preliminary results of the usability of deuterium oxide and bio-impedance analysis – a pilot analysis - Kim Pauwaert; Samuel Bodé; Upeshka Sewwandi Alwis; Toon Mylle; Pascal Boeckx; Joris Delanghe; Karel Everaert; Saskia Roggeman (Isotopes in Environmental and Health Studies, 2022)

Lianas and trees exhibit divergent intrinsic water‐use efficiency along elevational gradients in South American and African tropical forests - Francis M. Mumbanza; Marijn Bauters; Félicien Meunier; Pascal Boeckx; Lucas A. Cernusak; Hannes P. T. De Deurwaerder; Miro Demol; Camille Meeussen; Bram Sercu; Lore T. Verryckt; Jana Pauwels; Landry N. Cizungu; et al. (Global Ecology and Biogeography, 2021)
Aim Elevational gradients provide excellent opportunities to explore long‐term morphological and physiological responses of plants to environmental change. We determined the difference in the elevational pattern of foliar carbon isotope composition (δ 13 C) between lianas and trees, and assessed whether this difference arises from changes in photosynthesis or stomatal conductance. We also explored the pattern of nutrient limitations with the elevation of these two growth forms. Location The study was conducted in two mountain forests situated in the Neotropics and Palaeotropics. Time period August–September 2015 and August–October 2016. Major taxa studied Lianas and trees. Methods We conducted inventories of lianas and trees using standardized techniques along elevational gradients in Ecuador and Rwanda. We determined the values of several foliar traits including δ 13 C and chemical traits in dominant liana and tree species. We set up Bayesian linear mixed‐effect models to quantify the effects of elevation and growth form on each of the foliar traits , and the difference of the effect of elevation between the two growth forms (lianas and trees). Results We found consistent growth form specific divergences in foliar δ 13 C and carbon to nitrogen ratio (C : N) responses to elevation. While we noted a meaningful increase in foliar δ 13 C and C : N with elevation for trees, lianas did not exhibit such a trend. Foliar δ 13 C and C : N remained relatively constant for lianas along the transects. Main conclusions Lianas operate at relatively constant intrinsic water‐ and nitrogen‐use efficiencies with elevation compared with trees. Altogether, the study suggests the existence of a functional divergence of water and nutrient use strategies between lianas and trees along tropical elevational transects.

Soil Nutrient Depletion and Tree Functional Composition Shift Following Repeated Clearing in Secondary Forests of the Congo Basin - Marijn Bauters; Pieter Moonen; Laura Summerauer; Sebastian Doetterl; Daniel Wasner; Marco Griepentrog; Francis M. Mumbanza; Elizabeth Kearsley; Corneille Ewango; Faustin Boyemba; Johan Six; Bart Muys; et al. (Ecosystems, 2021)

Physico-chemical soil attributes under conservation agriculture and integrated soil fertility management - Eunice A. Mutuku; Bernard Vanlauwe; Dries Roobroeck; Pascal Boeckx; Wim M. Cornelis (Nutrient Cycling in Agroecosystems, 2021)

High photosynthetic capacity of Sahelian C3 and C4 plants - Thomas Sibret; Wim Verbruggen; Marc Peaucelle; Lore T. Verryckt; Marijn Bauters; Marie Combe; Pascal Boeckx; Hans Verbeeck (Photosynthesis Research, 2021)

Nitrogen transformation and pathways in the shallow groundwater–soil system within agricultural landscapes - Evgeniya Soldatova; Yihui Dong; Jiale Li; Yajie Liu; Jinjing Zan; Pascal Boeckx; Zhanxue Sun (Environmental Geochemistry and Health, 2021)

Sediment source fingerprinting: benchmarking recent outputs, remaining challenges and emerging themes - Adrian L. Collins; Martin Blackwell; Pascal Boeckx; Charlotte-Anne Chivers; Monica Emelko; Olivier Evrard; Ian Foster; Allen Gellis; Hamid Gholami; Steve Granger; Paul Harris; Arthur J. Horowitz; et al. (Journal of Soils and Sediments, 2020)
Purpose This review of sediment source fingerprinting assesses the current state-of-the-art, remaining challenges and emerging themes. It combines inputs from international scientists either with track records in the approach or with expertise relevant to progressing the science. Methods Web of Science and Google Scholar were used to review published papers spanning the period 2013–2019, inclusive, to confirm publication trends in quantities of papers by study area country and the types of tracers used. The most recent (2018–2019, inclusive) papers were also benchmarked using a methodological decision-tree published in 2017. Scope Areas requiring further research and international consensus on methodological detail are reviewed, and these comprise spatial variability in tracers and corresponding sampling implications for end-members, temporal variability in tracers and sampling implications for end-members and target sediment, tracer conservation and knowledge-based pre-selection, the physico-chemical basis for source discrimination and dissemination of fingerprinting results to stakeholders. Emerging themes are also discussed: novel tracers, concentration-dependence for biomarkers, combining sediment fingerprinting and age-dating, applications to sediment-bound pollutants, incorporation of supportive spatial information to augment discrimination and modelling, aeolian sediment source fingerprinting, integration with process-based models and development of open-access software tools for data processing. Conclusions The popularity of sediment source fingerprinting continues on an upward trend globally, but with this growth comes issues surrounding lack of standardisation and procedural diversity. Nonetheless, the last 2 years have also evidenced growing uptake of critical requirements for robust applications and this review is intended to signpost investigators, both old and new, towards these benchmarks and remaining research challenges for, and emerging options for different applications of, the fingerprinting approach.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

Tree species diversity improves beech growth and alters its physiological response to drought - Astrid Vannoppen; Kerstin Treydte; Pascal Boeckx; Vincent Kint; Quentin Ponette; Kris Verheyen; Bart Muys (Trees, 2020)

Century‐long apparent decrease in intrinsic water‐use efficiency with no evidence of progressive nutrient limitation in African tropical forests - Marijn Bauters; Sofie Meeus; Matti Barthel; Piet Stoffelen; Hannes P. T. De Deurwaerder; Félicien Meunier; Travis W. Drake; Quentin Ponette; Jerôme Ebuy; Pieter Vermeir; Hans Beeckman; Francis wyffels; et al. (Global Change Biology, 2020)
Forests exhibit leaf‐ and ecosystem‐level responses to environmental changes. Specifically, rising carbon dioxide (CO 2 ) levels over the past century are expected to have increased the intrinsic water‐use efficiency (iWUE) of tropical trees while the ecosystem is gradually pushed into progressive nutrient limitation. Due to the long‐term character of these changes, however, observational datasets to validate both paradigms are limited in space and time. In this study, we used a unique herbarium record to go back nearly a century and show that despite the rise in CO 2 concentrations, iWUE has decreased in central African tropical trees in the Congo Basin. Although we find evidence that points to leaf‐level adaptation to increasing CO 2 —that is, increasing photosynthesis‐related nutrients and decreasing maximum stomatal conductance, a decrease in leaf δ 13 C clearly indicates a decreasing iWUE over time. Additionally, the stoichiometric carbon to nitrogen and nitrogen to phosphorus ratios in the leaves show no sign of progressive nutrient limitation as they have remained constant since 1938, which suggests that nutrients have not increasingly limited productivity in this biome. Altogether, the data suggest that other environmental factors, such as increasing temperature, might have negatively affected net photosynthesis and consequently downregulated the iWUE. Results from this study reveal that the second largest tropical forest on Earth has responded differently to recent environmental changes than expected, highlighting the need for further on‐ground monitoring in the Congo Basin.

Regulation of nitrogen fixation from free-living organisms in soil and leaf litter of two tropical forests of the Guiana shield - Leandro Van Langenhove; Thomas Depaepe; Sara Vicca; Joke van den Berge; Clement Stahl; Elodie Courtois; James Weedon; Ifigenia Urbina; Oriol Grau; Dolores Asensio; Josep Peñuelas; Pascal Boeckx; et al. (Plant and Soil, 2020)

Land use controls Kenyan riverine nitrate discharge into Lake Victoria – evidence from Nyando, Nzoia and Sondu Miriu river catchments - Benjamin Nyilitya; Stephen Mureithi; Pascal Boeckx (Isotopes in Environmental and Health Studies, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Larger direct than indirect effects of multiple environmental changes on leaf nitrogen of forest herbs - Haben Blondeel; Elyn Remy; Michael P. Perring; Dries Landuyt; Samuel Bodé; Pieter De Frenne; Pascal Boeckx; Kris Verheyen (Plant and Soil, 2019)

Drivers of increased soil erosion in East Africa’s agro-pastoral systems: changing interactions between the social, economic and natural domains - Maarten Wynants; Claire Kelly; Kelvin Mtei; Linus Munishi; Aloyce Patrick; Anna Rabinovich; Mona Nasseri; David Gilvear; Neil Roberts; Pascal Boeckx; Geoff Wilson; William H. Blake; et al. (Regional Environmental Change, 2019)

Isotope fractionation during root water uptake by Acacia caven is enhanced by arbuscular mycorrhizas - María Poca; Olivia Coomans; Carlos Urcelay; Sebastián R. Zeballos; Samuel Bodé; Pascal Boeckx (Plant and Soil, 2019)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Unraveling the genetic background of the Yangambi Research Center cacao germplasm collection, DR Congo - Hayley Rottiers; Helena Everaert; Pascal Boeckx; Gaston Limba; Geert Baert; Jocelyn De Wever; Kevin Maebe; Guy Smagghe; Koen Dewettinck; Kathy Messens (Tree Genetics & Genomes, 2018)

Constraints for future cocoa production in Ghana - John Edem Kongor; Hans De Steur; Davy Van de Walle; Xavier Gellynck; Emmanuel Ohene Afoakwa; Pascal Boeckx; Koen Dewettinck (Agroforestry Systems, 2018)

The Younger Dryas and Preboreal landscape in the Moervaart area (northwestern Belgium) and the apparent decrease in human occupation - Johanna A. A. Bos; Vanessa Gelorini; Thijs van der Meeren; Jolien Peleman; Mona Court-Picon; Hendrik Demiddele; Philippe De Smedt; Mathieu Boudin; Jacques Verniers; Pascal Boeckx; Philippe Crombé (Vegetation History and Archaeobotany, 2018)

Driving Factors Behind Litter Decomposition and Nutrient Release at Temperate Forest Edges - Elyn Remy; Karen Wuyts; Lotte Van Nevel; Pallieter De Smedt; Pascal Boeckx; Kris Verheyen (Ecosystems, 2018)

Landscape-scale assessments of stable carbon isotopes in soil under diverse vegetation classes in East Africa: application of near-infrared spectroscopy - Leigh Ann Winowiecki; Tor-Gunnar Vågen; Pascal Boeckx; Jennifer A. J. Dungait (Plant and Soil, 2017)

Functional Composition of Tree Communities Changed Topsoil Properties in an Old Experimental Tropical Plantation - Marijn Bauters; Hans Verbeeck; Sebastian Doetterl; Evy Ampoorter; Geert Baert; Pieter Vermeir; Kris Verheyen; Pascal Boeckx (Ecosystems, 2017)

Methodological perspectives on the application of compound-specific stable isotope fingerprinting for sediment source apportionment - Hari R. Upadhayay; Samuel Bodé; Marco Griepentrog; Dries Huygens; Roshan M. Bajracharya; William H. Blake; Gerd Dercon; Lionel Mabit; Max Gibbs; Brice X. Semmens; Brian C. Stock; Wim Cornelis; et al. (Journal of Soils and Sediments, 2017)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

Pathway of nitrous oxide consumption in isolated P seudomonas stutzeri strains under anoxic and oxic conditions - Joachim Desloover; Dries Roobroeck; Kim Heylen; Sebastià Puig; Pascal Boeckx; Willy Verstraete; Nico Boon (Environmental Microbiology, 2014)
Summary The microbial consumption of nitrous oxide ( N 2 O ) has gained great interest since it was revealed that this process could mitigate the greenhouse effect of N 2 O . The consumption of N 2 O results from its reduction to dinitrogen gas ( N 2 ) as part of the denitrification process. However, there is ongoing debate regarding an alternative pathway, namely reduction of N 2 O to NH 4 + , or assimilatory N 2 O consumption. To date, this pathway is poorly investigated and lacks unambiguous evidence. Enrichment of denitrifying activated sludge using a mineral nitrogen‐free medium rendered a mixed culture capable of anoxic and oxic N 2 O consumption. Dilution plating, isolation and deoxyribonucleic acid fingerprinting identified a collection of P seudomonas stutzeri strains as dominant N 2 O consumers in both anaerobic and aerobic enrichments. A detailed isotope tracing experiment with a P seudomonas stutzeri isolate showed that consumption of N 2 O via assimilatory reduction to NH 4 + was absent. Conversely, respiratory N 2 O reduction was directly coupled to N 2 fixation.

Nitrogen and phosphorus benefits from faba bean (Vicia faba L.) residues to subsequent wheat crop in the humid highlands of Ethiopia - Amsalu Nebiyu; Adeline Vandorpe; Jan Diels; Pascal Boeckx (Nutrient Cycling in Agroecosystems, 2014)

Importance of correct B value determination to quantify biological N2 fixation and N balances of faba beans (Vicia faba L.) via 15N natural abundance - Amsalu Nebiyu; Dries Huygens; Hari Ram Upadhayay; Jan Diels; Pascal Boeckx (Biology and Fertility of Soils, 2014)

Translocation and turnover of rhizodeposit carbon within soil microbial communities of an extensive grassland ecosystem - Wajira K. Balasooriya; Karolien Denef; Dries Huygens; Pascal Boeckx (Plant and Soil, 2014)

Nitrogen deposition promotes the production of new fungal residues but retards the decomposition of old residues in forest soil fractions - Marco Griepentrog; Samuel Bodé; Pascal Boeckx; Frank Hagedorn; Alexander Heim; Michael W. I. Schmidt (Global Change Biology, 2014)
Atmospheric nitrogen ( N ) deposition has frequently been observed to increase soil carbon ( C ) storage in forests, but the underlying mechanisms still remain unclear. Changes in microbial community composition and substrate use are hypothesized to be one of the key mechanisms affected by N inputs. Here, we investigated the effects of N deposition on amino sugars, which are used as biomarkers for fungal‐ and bacterial‐derived microbial residues in soil. We made use of a 4‐year combined CO 2 enrichment and N deposition experiment in model forest ecosystems, providing a distinct 13 C signal for ‘new’ and ‘old’ C in soil organic matter and microbial residues measured in density and particle‐size fractions of soils. Our hypothesis was that N deposition decreases the amount of fungal residues in soils, with the new microbial residues being more strongly affected than old residues. The soil fractionation showed that organic matter and microbial residues are mainly stabilized by association with soil minerals in the heavy and fine fractions. Moreover, the bacterial residues are relatively enriched at mineral surfaces compared to fungal residues. The 13 C tracing indicated a greater formation of fungal residues compared to bacterial residues after 4 years of experiment. In contradiction to our hypotheses, N deposition significantly increased the amount of new fungal residues in bulk soil and decreased the decomposition of old microbial residues associated with soil minerals. The preservation of old microbial residues could be due to decreased N limitation of microorganisms and therefore a reduced dependence on organic N sources. This mechanism might be especially important in fine heavy fractions with low C / N ratios, where microbial residues are effectively protected from decomposition by association with soil minerals.

Nutrient input from hemiparasitic litter favors plant species with a fast-growth strategy - Andreas Demey; Jeroen Staelens; Lander Baeten; Pascal Boeckx; Martin Hermy; Jens Kattge; Kris Verheyen (Plant and Soil, 2013)

Effects of two contrasting hemiparasitic plant species on biomass production and nitrogen availability - Andreas Demey; Els Ameloot; Jeroen Staelens; An De Schrijver; Gorik Verstraeten; Pascal Boeckx; Martin Hermy; Kris Verheyen (Oecologia, 2013)

Carbon and nitrogen mass balance during flue gas treatment with Dunaliella salina cultures - Till Harter; Peter Bossier; Johan Verreth; Samuel Bodé; David Van der Ha; Ann-Eline Debeer; Nico Boon; Pascal Boeckx; Wim Vyverman; Nancy Nevejan (Journal of Applied Phycology, 2013)

Temporal variation of rhizodeposit-C assimilating microbial communities in a natural wetland - Wajira K. Balasooriya; Dries Huygens; Karolien Denef; Dries Roobroeck; Niko E. C. Verhoest; Pascal Boeckx (Biology and Fertility of Soils, 2013)

Improving the management of nitrate pollution in water by the use of isotope monitoring: the δ 15 N, δ 18 O and δ 11 B triptych - David Widory; Emmanuelle Petelet-Giraud; Agnes Brenot; Jan Bronders; Kristof Tirez; Pascal Boeckx (Isotopes in Environmental and Health Studies, 2013)

Canopy Uptake of 15NH3 by Four Temperate Tree Species and the Interaction with Leaf Properties - Sandy Adriaenssens; Jeroen Staelens; Karen Wuyts; Shari Van Wittenberghe; Tatiana Wuytack; Kris Verheyen; Pascal Boeckx; Roeland Samson (Water, Air, & Soil Pollution, 2012)

Retention of Dissolved Inorganic Nitrogen by Foliage and Twigs of Four Temperate Tree Species - Sandy Adriaenssens; Jeroen Staelens; Karen Wuyts; Roeland Samson; Kris Verheyen; Pascal Boeckx (Ecosystems, 2012)

Spatial variability and biophysicochemical controls on N2O emissions from differently tilled arable soils - Mohammad Mofizur Rahman Jahangir; Dries Roobroeck; Oswald Van Cleemput; Pascal Boeckx (Biology and Fertility of Soils, 2011)

Foliar Nitrogen Uptake from Wet Deposition and the Relation with Leaf Wettability and Water Storage Capacity - Sandy Adriaenssens; Jeroen Staelens; Karen Wuyts; An de Schrijver; Shari Van Wittenberghe; Tatiana Wuytack; Fatemeh Kardel; Kris Verheyen; Roeland Samson; Pascal Boeckx (Water, Air, & Soil Pollution, 2011)

Isotopes for improved management of nitrate pollution in aqueous resources: review of surface water field studies - Angelika Nestler; Michael Berglund; Frederik Accoe; Steluta Duta; Dongmei Xue; Pascal Boeckx; Philip Taylor (Environmental Science and Pollution Research, 2011)

Microbial nitrogen dynamics in south central Chilean agricultural and forest ecosystems located on an Andisol - Dries Huygens; Dries Roobroeck; Lynn Cosyn; Francisco Salazar; Roberto Godoy; Pascal Boeckx (Nutrient Cycling in Agroecosystems, 2011)

Impact of hemiparasitic Rhinanthus angustifolius and R. minor on nitrogen availability in grasslands - Els Ameloot; Greet Verlinden; Pascal Boeckx; Kris Verheyen; Martin Hermy (Plant and Soil, 2008)

N2O emission from conventional and minimum-tilled soils - Daan Beheydt; Pascal Boeckx; Hasan Pervej Ahmed; Oswald Van Cleemput (Biology and Fertility of Soils, 2008)

Response of CH4 oxidation and methanotrophic diversity to NH4 + and CH4 mixing ratios - Svetlana Bykova; Pascal Boeckx; Irina Kravchenko; Valery Galchenko; Oswald Van Cleemput (Biology and Fertility of Soils, 2007)

Influence of DCD and DMPP on soil N dynamics after incorporation of vegetable crop residues - Barbara Chaves; Andrews Opoku; Stefaan De Neve; Pascal Boeckx; Oswald Van Cleemput; Georges Hofman (Biology and Fertility of Soils, 2006)

Assessment of Temporal and Spatial Variation of Nitrate Removal in Riparian Zones - Karel Dhondt; Pascal Boeckx; Niko E. C. Verhoest; Georges Hofman; Oswald Van Cleemput (Environmental Monitoring and Assessment, 2006)

The effect of mixing organic biological waste materials and high-N crop residues on the short-time N2O emission from horticultural soil in model experiments - Barbara Chaves; Stefaan De Neve; Maria del Carmen Lillo Cabrera; Pascal Boeckx; Oswald Van Cleemput; Georges Hofman (Biology and Fertility of Soils, 2005)

Temporal and spatial patterns of denitrification enzyme activity and nitrous oxide fluxes in three adjacent vegetated riparian buffer zones - Karel Dhondt; Pascal Boeckx; Georges Hofman; Oswald Van Cleemput (Biology and Fertility of Soils, 2004)

Soil properties influencing the denitrification potential of Flemish agricultural soils - Karoline D'Haene; Edwin Moreels; Stefaan De Neve; Barbara Chaves Daguilar; Pascal Boeckx; Georges Hofman; Oswald Van Cleemput (Biology and Fertility of Soils, 2003)

Long‐term effects of mineral versus organic fertilizers on activity and structure of the methanotrophic community in agricultural soils - Dave Seghers; Eva M. Top; Dirk Reheul; Robert Bulcke; Pascal Boeckx; Willy Verstraete; Steven D. Siciliano (Environmental Microbiology, 2003)
Summary Agricultural practices, such as mineral nitrogen fertilization, have an impact on the soil's ability to oxidize methane, but little is known about the shifts in the methanotrophic community composition associated with these practices. Therefore, the long‐term effect of both mineral (NH 4 NO 3 ) and organic (manure and GFT‐compost) fertilizer applications on the soil methanotrophic community activity and structure were investigated. Both high and low affinity methane oxidation rates were lower in the soil treated with mineral fertilizer compared to the other soils. An enhanced nitrate concentration was observed in the mineral fertilized soil but nitrate did not show a direct affect on the high affinity methane oxidation. In contrast, the low affinity methane oxidation was slowed down by increased nitrate concentrations, which suggests a direct effect of nitrate on low affinity methane oxidation. Denaturing gradient gel electrophoresis (DGGE) analysis of 16S rRNA gene fragments specific for methanotrophs revealed a distinct community between the mineral and organic fertilized soils as extra Type I methanotrophic bands (phylotypes) became visible in the organic fertilized soils. These phylotypes were not visible in the patterns of the added organic fertilizers suggesting an indirect effect of the organic fertilizers on the methanotrophic community. Additionally, a molecular analysis was performed after the low affinity methane oxidation test. The enhanced methane concentrations used in the test enriched certain low affinity methanotrophs in the organic fertilized soils but not in the mineral fertilized soil. Supporting the molecular and functional observations, fatty acids characteristic for methanotrophs were less abundant in the soil treated with mineral fertilizer compared to the soil treated with compost. In conclusion, the function and molecular and chemical composition of the methanotrophic community are all altered in soil fertilized with mineral fertilizer.

Carbon stock changes and carbon sequestration potential of Flemish cropland soils - Steven Sleutel; Stefaan De Neve; Georges Hofman; Pascal Boeckx; Daan Beheydt; Oswald Van Cleemput; Inge Mestdagh; Peter Lootens; Lucien Carlier; Nancy Van Camp; Hans Verbeeck; Inge Vande Walle; et al. (Global Change Biology, 2003)
Evaluations of soil organic carbon (SOC) stocks are often based on assigning a carbon density to each one of a number of ecosystems or soil classes considered, using data from soil profiles within these categories. A better approach, in which the use of classification methods by which extrapolation of SOC data to larger areas is avoided, can only be used if enough data are available at a sufficiently small scale. Over 190 000 SOC measurements (0–24 cm) have been made in the Flemish cropland (the Northern part of Belgium) in the 1989–2000 period. These SOC data were grouped into 3‐year periods and as means plus standard deviation per (part of) community (polygons). This large dataset was used to calculate SOC stocks and their evolution with time, without data extrapolation. Using a detailed soil map, larger spatial groups of polygons were created based on soil texture and spatial location. Linear regression analysis showed that in the entire study area, SOC stocks had decreased or at best had remained stable. In total, a yearly decrease of 354 kton OC yr −1 was calculated, which corresponds with a net CO 2 emission of 1238 kton CO 2 yr −1 . Specific regions with a high carbon sequestration potential were identified, based on SOC losses during the 1989–2000 period and the mean 1999 SOC content, compared to the average SOC content of soils in Flanders with a similar soil texture. When restoring the SOC stocks to their 1990 level, we estimated the carbon sequestration potential of the Flemish cropland soils to be some 300 kton CO 2 yr −1 at best, which corresponds to a 40‐year restoration period. In conclusion, we can say that in regions where agricultural production is very intense, carbon sequestration in the cropland may make only a very modest contribution to a country's effort to reduce greenhouse gas emissions.

Urease and nitrification inhibitors to reduce emissions of CH4 and N2O in rice production - Xingkai Xu; Pascal Boeckx; Oswald Van Cleemput; Likai Zhou (Nutrient Cycling in Agroecosystems, 2002)

Use of principal component analysis to assess factors controlling net N mineralization in deciduous and coniferous forest soils - Hilde Vervaet; Bernard Massart; Pascal Boeckx; Oswald Van Cleemput; Georges Hofman (Biology and Fertility of Soils, 2002)

Two-year field study on the emission of N2O from coarse and middle-textured Belgian soils with different land use - Annick Goossens; Alex De Visscher; Pascal Boeckx; Oswald Van Cleemput (Nutrient Cycling in Agroecosystems, 2001)

Spatial and sectorial disaggregation of N2O emissions from agriculture in Belgium - Pascal Boeckx; Eline Van Moortel; Oswald Van Cleemput (Nutrient Cycling in Agroecosystems, 2001)

Estimates of N2O and CH4 fluxes from agricultural lands in various regions in Europe - Pascal Boeckx; Oswald Van Cleemput (Nutrient Cycling in Agroecosystems, 2001)

Nitrous oxide emission from herbicide-treated soybean - Zhang Lifeng; Pascal Boeckx; C. Guanxiong; Oswald Van Cleemput (Biology and Fertility of Soils, 2000)